2017
DOI: 10.1002/pssa.201700404
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TiO2 Nanorods for Schottky‐Type UV‐Photodetectors and Third‐Generation Solar Cells

Abstract: TiO2 nanorods (NRs) are successfully synthesized on fluorine‐doped tin‐oxide pre‐coated glass substrates via hydrothermal technique. The effect of growth parameters on morphology of the synthesized NRs is investigated in detail. The results revealed that critical values for temperature, growth‐time, acidity, and precursor concentration are required for the synthesis of well‐aligned TiO2 NRs. Following the optimization of growth parameters, the well‐oriented TiO2 NRS are decorated with a thin‐sputtered layer of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Zou et al studied a TiO 2 /Ag-based Schottky-type photodetector and observed high responsivity (∼13 A/W) with fast response (time of 0.5 s) and recovery (time of 0.7 s). Guller et al have also studied the TiO 2 /Ag Schottky junction photodetector, and they found a high photocurrent value under UV light illumination (λ ∼ 380 nm), with responsivity of 3 A/W at an external bias of −1 V. A double-layered TiO 2 nanostructure/Au Schottky-contact-based UV photodetector was reported by Wang et al In spite of having fast response and good UV sensing properties, TiO 2 /novel metal-based Schottky junction photodetectors suffer from high fabrication cost, which arises because of the costly novel metals as well as expensive metal deposition techniques. …”
Section: Introductionmentioning
confidence: 99%
“…Zou et al studied a TiO 2 /Ag-based Schottky-type photodetector and observed high responsivity (∼13 A/W) with fast response (time of 0.5 s) and recovery (time of 0.7 s). Guller et al have also studied the TiO 2 /Ag Schottky junction photodetector, and they found a high photocurrent value under UV light illumination (λ ∼ 380 nm), with responsivity of 3 A/W at an external bias of −1 V. A double-layered TiO 2 nanostructure/Au Schottky-contact-based UV photodetector was reported by Wang et al In spite of having fast response and good UV sensing properties, TiO 2 /novel metal-based Schottky junction photodetectors suffer from high fabrication cost, which arises because of the costly novel metals as well as expensive metal deposition techniques. …”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Meanwhile, the construction of ultrahigh-performance photodetectors based on a 1D structure with Schottky junction has attracted much attention. [8][9][10][11] The problem of charge recombination due to the lattice mismatch between the n-layer and p-layer is overcome, however, the high state density at the TiO 2 surface will cause nonradiative charge recombination. [12] Due to the huge surface-area to volume ratios of TiO 2 NR and the dangling bonds at the surface, the holetrapping mechanism through oxygen adsorption and desorption [13,14] drastically prolongs the device response time.…”
mentioning
confidence: 99%
“…These values are much higher (slower) as compared to the NTs based devices and may not be suitable for future generation faster device applications. The slow response may be due to the presence of surface defects or the slow process of oxygen adsorption or desorption in NRs [21]. These surface defects may restrict the photodetection and block the transport of photogenerated carriers, which resulted in recombination centres for them and degrade the photodetection property [17,21].…”
Section: Resultsmentioning
confidence: 99%
“…The slow response may be due to the presence of surface defects or the slow process of oxygen adsorption or desorption in NRs [21]. These surface defects may restrict the photodetection and block the transport of photogenerated carriers, which resulted in recombination centres for them and degrade the photodetection property [17,21]. It is also noteworthy to mention that the bandgap of TiO 2 NRs is 3 eV [55], which has been deviated from the UV region and gets closer to the visible region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation